Transcriptome Analysis Reveals Candidate Genes Related to Color Fading of ‘Red Bartlett’ (Pyrus communis L.) - Wang, Zhigang; Du, Hong; Zhai, Rui; Song, Linyan; Ma, Fengwang; Xu, Lingfei (Frontiers in Plant Science, 2017)
The red color of fruit is an attractive plant trait for consumers. Plants with color-faded fruit have a lower commercial value, such as ‘Red Bartlett’ pears (Pyrus communis L.) that have dark-red fruit in the early stages of fruit development that subsequently fade to red-green at maturity. To identify the reason for color fading, we first analyzed the anthocyanin content of peel from ‘Red Bartlett,’ which displays the color fading phenomenon, and ‘Starkrimson,’ which has no color fading. Results showed that the anthocyanin content of ‘Red Bartlett’ peel decreased significantly late in fruit development, while in ‘Starkrimson’ there was no significant decrease. Next, RNA-Sequencing was used to identify 947 differentially expressed genes (DEGs) between ‘Red Bartlett’ and ‘Starkrimson.’ Among them, 471 genes were upregulated and 476 genes were downregulated in ‘Red Bartlett’ at the late development stage relative to ‘Starkrimson.’ During ‘Red Bartlett’ color fading, the structural gene LDOX and six GST family genes were downregulated, while FLS, LAC, POD, and five light-responding genes were significantly upregulated. Additionally, 45 genes encoding transcription factors MYB, bHLH, WRKY, NAC, ERF, and zinc finger were identified among 947 DEGs. Changes in the expression of these genes may be responsible for the decrease in anthocyanin accumulation in ‘Red Bartlett’ fruit. Taken together, this study demonstrated that color fading of ‘Red Bartlett’ was closely linked to reduced anthocyanin biosynthesis, increased anthocyanin degradation and suppression of anthocyanin transport. It also provided novel evidence for the involvement of light signals in the color fading of red-skinned pears.